Diagnosis of autism in a rare case of tyrosine hydroxylase deficiency: a case report - Zoe Maria Dominique Reyes; Emma Lynch; Julia Henry; Lenika Marina De Simone; Sarah A. Sobotka (BMC, 2023)
Abstract Background Tyrosine hydroxylase deficiency (THD) is a rare movement disorder with broad phenotypic expression caused by bi-allelic mutations in the TH gene, which encode for tyrosine hydroxylase (TH) protein. Some patients with THD have improvement in dystonia with carbidopa-levodopa, a synthetic form of dopamine typically used in Parkinson's disease, and are considered to have dopa-responsive THD. THD has been found in 0.5-1 per million persons, although due to overlapping symptoms with other disorders and the need for genetic testing, prevalence is likely underestimated. Existing literature describes some patients with THD having intellectual disability, but comorbid autism spectrum disorder (ASD) has not been reported. Case presentation A nearly 3-year-old boy was referred to pediatric neurology due to hypotonia, delayed motor milestones, and expressive speech delay. Whole exome sequencing confirmed tyrosine hydroxylase deficiency, detecting a novel variant p.S307C first reported here. The child was treated with carbidopa-levodopa with an excellent response, resulting in improved balance, fewer falls, and improved ability to jump, run and climb stairs. He was determined to have dopa-responsive THD. Due to his delays in expressive speech, the boy also had an assessment with a developmental and behavioral pediatrician, who identified a pattern of social pragmatic speech delay, sensory sensitivities, and restricted interests, and determined that he met criteria for a diagnosis of ASD. Conclusions While ASD can stand alone as a clinical diagnosis, it is also a cardinal feature of other genetically-based neurological disorders. To our knowledge, this is the first case that describes a patient with both disorders. Perhaps THD may be among the genetic disorders linked with ASD.